2021
DOI: 10.1001/jamanetworkopen.2021.3594
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Renin-Angiotensin-Aldosterone System Inhibitors and Clinical Outcomes in Patients With COVID-19

Abstract: Key Points Question Is the receipt of angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) associated with worse clinical outcomes among patients with COVID-19? Findings In this systematic review and meta-analysis of 52 studies that evaluated clinical outcomes among 101 949 total patients with COVID-19 who did and did not receive ACEIs or ARBs, a significantly lower risk of multivariable-adjusted mortality and severe adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
90
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 77 publications
8
90
0
8
Order By: Relevance
“…Angiotensin receptor blockers (ARBs) showed a significant association with increased in-hospital mortality (Supplementary Table S4). Observational studies of renin-angiotensin-aldosterone system inhibitors and association with COVID-19 outcomes have tended to be associated with neutral to reduced risk of COVID-19 hospitalization or mortality rather than increased risk as noted in our analyses [ 37 , 38 ]. However, most of the reviewed studies were not exclusively examining a T2D population, and limited prospective evidence on this topic remains.…”
Section: Discussionmentioning
confidence: 90%
“…Angiotensin receptor blockers (ARBs) showed a significant association with increased in-hospital mortality (Supplementary Table S4). Observational studies of renin-angiotensin-aldosterone system inhibitors and association with COVID-19 outcomes have tended to be associated with neutral to reduced risk of COVID-19 hospitalization or mortality rather than increased risk as noted in our analyses [ 37 , 38 ]. However, most of the reviewed studies were not exclusively examining a T2D population, and limited prospective evidence on this topic remains.…”
Section: Discussionmentioning
confidence: 90%
“…These patients tend to have positive relation with hypotension at admission and negative relation with hypertension as preexisting disease suggesting a relation between tension regulation and the level of SARS-COV2 in lungs. Recently a meta-analysis showed an association between Renin–Angiotensin–Aldosterone System inhibitors and clinical outcomes in patients with COVID-19 [ 41 ]. Activation of MHC class I antigen processing and presentation during the innate immune response implicated all components of the proteasome, but a particularly pronounced correlation was detected between levels of SARS-CoV-2 RNA and activation of components of the immunoproteasome.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although it was initially assumed that ACE inhibitors and angiotensin receptor blockers to treat hypertension or cardiovascular conditions might exacerbate COVID-19 infection and lead to worse outcomes, the most recent available meta-analysis did not confirm this higher risk. 11 Finally, it has been suggested that modulating TMPRSS2 expression through specific antibodies or non-coding RNAs could prevent virus entry into host cells, 11 12 but these potential therapeutic options are still under investigation.…”
Section: Introductionmentioning
confidence: 99%